APLIKASI PETA PEMIKIRAN I-THINK DALAM MENINGKATKAN KEMAHIRAN BERFIKIR ARAS TINGGI (KBAT) - Zakaria, Normah; Ali, Azita; Hamidon, Nur Izeanty; Abd Rasap, Suhaili (Online Journal for TVET Practitioners, 2018)
Higher-order thinking skills (HOTS) is one of the processes or activities in teaching and learning at present. KBAT is the ability to apply the knowledge, skills and values in making of reasoning and reflection for problem solving, decision making, innovative and able to create something. These skill require understanding and mastering teachers to develop them or implement in the teaching and learning of each days. Therefore, the class or the teacher is an agent of change for achieving the Ministry of Education and the Education Development Plan (Pelan Pembangunan Pendidikan Malaysia) to improve the performance of national education. Hence, this study aims to see the change in terms of understanding student achievement, interest and have reflective thinking to enhance higher-order thinking skills (HOTS) among students for the topic ‘The Solar System’ in Science Year 4 and in particular to improve cultivate thinking skills among students to produce students who have creative thinking, critical thinking and innovation. Therefore, this study will discuss the effectiveness of i-think techniques in the context of teaching and learning of science subjects. In addition, this study also looked at the extent to which this application can improve thinking skills, enthusiasm, empathy and reflective thinking of students on these subjects. Samples are also a study population, consisted of 36 students of Year 4 Mars SK St. Francis, Melaka. The data were collected from the respondents using the questionnaires and the achievements of set pre and posttest. The study showed the students achievement has undergone changes towards positive after application map i-Think thinking in teaching and learning. Increasing marks that occur show that use of i-Think as a method of teaching which is practiced among teachers of science